Immune‐Checkpoint‐Inhibitor‐Related Bullous Pemphigoid During Avelumab Maintenance Therapy in a Patient With Metastatic Renal Pelvic Carcinoma: A Case Report - Taketoshi Nara; Kengo Furihata; Akane Kikuchi; Yuya Sekine; Hiromi Sato; Mizuki Kobayashi; Ryohei Yamamoto; Mitsuru Saito; Shintaro Narita; Tomonori Habuchi (IJU Case Reports, 2026)
ABSTRACT Introduction Bullous pemphigoid is a rare cutaneous, immune‐related adverse event, and avelumab‐associated cases are extremely rare. Case Presentation A 76‐year‐old man receiving avelumab maintenance therapy for recurrent renal pelvic carcinoma developed pruritic erythema and tense blisters 20 days after the first dose. Laboratory examination showed eosinophilia, increased immunoglobulin E level, and markedly elevated anti‐BP180 antibodies. Moreover, skin biopsy revealed subepidermal blistering with eosinophilic infiltration, supporting drug‐associated bullous pemphigoid. Prednisolone (15 mg/day, increased to 25 mg/day) led to marked improvement. After the second course, avelumab was discontinued, and no recurrence occurred. Conclusion Immune‐checkpoint‐inhibitor‐related, drug‐associated bullous pemphigoid can present with nonspecific symptoms before blistering. Thus, urologists should monitor skin changes during immune checkpoint inhibitor therapy and promptly involve dermatology.